Humoral Immune Response following Seasonal Influenza Vaccine in Islet Transplant Recipients. Issue 3 (March 2013) - Silva, Moacyr; Humar, Atul; Shapiro, A. M. James; Senior, Peter; Hoschler, Katja; Baluch, Aliyah; Wilson, Leticia E.; Kumar, Deepali
Annual influenza vaccine is recommended for organ transplant recipients, but immunogenicity is known to be suboptimal. Islet transplant recipients receive immunosuppressive therapy, but there are no data on the immunogenicity of influenza vaccine in this population. In this prospective cohort study, adult islet transplant recipients at least 3 months posttransplant were enrolled. All patients received the 2010–2011 seasonal influenza vaccine. Serum was obtained pre- and postvaccination to determine humoral response to each of the three influenza strains included in the vaccine. Adverse effects of vaccine were also noted. A total of 61 islet transplant recipients were enrolled and completed the study protocol. The median time from last transplant was 1.9 years (range 0.26–11.4 years), and most patients had undergone multiple prior islet transplant procedures (90.2%). Overall immunogenicity of the vaccine was poor. Seroconversion rates to H1N1, H3N2, and B antigens were 34.4%, 29.5%, and 9.8%, respectively. In the subset not seroprotected at baseline, a protective antibody titer postvaccination was achieved in 58.6%, 41.9%, and 34.5% of patients, respectively. Patients within the first year of transplant were significantly less likely to seroconvert to at least one antigen (23.5% vs. 54.5%; p = 0.029). Alemtuzumab recipients trended toward lower seroconversion rates (25% vs. 51%; p = 0.11). No vaccine-related safety concerns were identified. Seasonal influenza vaccine had suboptimal immunogenicity in islet transplant recipients especially those who were less than 1 year posttransplant or had received alemtuzumab induction. Novel strategies for protection in this group of patients need further study.